Standardisation and consensus guidelines for minimal residual disease assessment in Philadelphia-positive acute lymphoblastic leukemia (Ph + ALL) by real-time quantitative reverse transcriptase PCR of e1a2 BCR-ABL1 - Pfeifer, Heike; Cazzaniga, G.; Velden, V. H. J. van der; Cayuela, J. M.; Schäfer, B.; Spinelli, O.; Akiki, S.; Avigad, S.; Bendit, I.; Borg, K.; Cavé, H.; Elia, L.; et al. (Leukemia, 2019)
Minimal residual disease (MRD) is a powerful prognostic factor in acute lymphoblastic leukemia (ALL) and is used for patient stratification and treatment decisions, but its precise role in Philadelphia chromosome positive ALL is less clear. This uncertainty results largely from methodological differences relating to the use of real-time quantitative PCR (qRT-PCR) to measure BCR-ABL1 transcript levels for MRD analysis. We here describe the first results by the EURO-MRD consortium on standardization of qRT-PCR for the e1a2 BCR-ABL1 transcript in Ph + ALL, designed to overcome the lack of standardisation of laboratory procedures and data interpretation. Standardised use of EAC primer/probe sets and of centrally prepared plasmid standards had the greatest impact on reducing interlaboratory variability. In QC1 the proportion of analyses with BCR-ABL1/ABL1 ratios within half a log difference were 40/67 (60%) and 52/67 (78%) at 10−3 and 36/67 (53%) and 53/67 (79%) at 10−4BCR-ABL1/ABL1. Standardized RNA extraction, cDNA synthesis and cycler platforms did not improve results further, whereas stringent application of technical criteria for assay quality and uniform criteria for data interpretation and reporting were essential. We provide detailed laboratory recommendations for the standardized MRD analysis in routine diagnostic settings and in multicenter clinical trials for Ph + ALL.
Published online: 11 March 2019
Gesehen am 25.05.2020